2016
DOI: 10.1007/s00248-016-0784-y
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Survival of Escherichia coli, Vibrio cholerae, Salmonella typhimurium and Shigella dysenteriae in Riverbed Sediments

Abstract: Studies on the survival of bacterial enteric pathogens in riverbed sediments have mostly focused on individual organisms. Reports on the competitive survival of these pathogens in riverbed sediments under the same experimental setup are limited. We investigated the survival of Escherichia coli, Salmonella enterica ser. Typhimurium, Vibrio cholerae and Shigella dysenteriae in riverbed sediments of the Apies River. Experiments were performed in flow chambers containing three sediment types and connected to aquar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
4
21
0
Order By: Relevance
“…Schematic representation of sediment chambers used for the laboratory resuspension experiments (Figure modified from Abia et al [38]).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Schematic representation of sediment chambers used for the laboratory resuspension experiments (Figure modified from Abia et al [38]).…”
Section: Figurementioning
confidence: 99%
“…and Vibrio cholerae have also been detected in riverbed sediments in South Africa, indicating the possible presence of these pathogenic organisms [37]. In a study conducted by Abia et al [38], the authors demonstrated through laboratory experiments that these pathogens could survive in the sediments of the Apies River for up to 30 days. Despite this finding, current monitoring of the country’s water resources (as with many developing countries) for microbial quality does not take into consideration sediment quality [39].…”
Section: Introductionmentioning
confidence: 99%
“…However, they vary spatially, depending on different aspects like environmental factors, community adaptation and human activities [2][3][4]. The dynamics of bacterial communities in developing countries are poorly understood [5,6] including the present study area: selected regions of the Bay of Bengal, Bangladesh.…”
Section: Introductionmentioning
confidence: 98%
“…Apart from rainfall, water temperature variations have been shown to affect the growth and survival dynamics of microbial organisms in raw water sources [26][27][28][29]. Variations in water temperature, which is controlled by factors such as air temperature, cloud cover, solar radiation and other geomorphometric factors [30,31], affect the hydrodynamic distribution of microorganisms through increased stratification [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%